The Effectiveness of the Minimal Pairs Technique in Learning Japanese Pronunciation - Wahyuni, Yuli; Indraswari, Thamita Islami (Journal of Japanese Language Education and Linguistics, 2022)
Distinguishing and pronouncing the sound of sha, sa, ja, za, tsu, double sounds, long sounds, nasal sounds, and youon sounds are still considered difficult for Japanese learners; it is becoming a problem because when the learners cannot distinguish the correct sounds in Japanese, it will result in an inability to pronounce and write Japanese sounds correctly. This study has tested the effectiveness of the minimal pairs technique in learning Japanese pronunciation and the learners's response to the technique. The research employed a quasi-experimental quantitative method by applying the minimal pairs technique to learn Japanese pronunciation in one class, Japanese level N5 or beginner level. The comparative statistical calculation result showed that the Minimal Pairs model is effective in improving Japanese pronunciation in long vowels, double consonants, semi-vowel sounds, tsu sounds, nasal sounds, and also helped the learners’ to understand differences in sa and sha line sounds and the difference between the sounds of the za and ja lines. The questionnaire result showed that the learners feel that the technique is quite tedious, but on the other hand, the technique is beneficial for them in learning and practicing Japanese pronunciation.